The Concept Of Veterinary-Sanitary Expertise And Its Place In The Training Of Veterinary Doctors. - Bekturova Nigorakhan Bakhtiyor Qizi; Mingliyev G'ayrat Akromvich (Genius Journals, 2024)
Veterinary-sanitary expertise is a science that studies methods of sanitary-hygienic assessment of animal products. The main task of the veterinary-sanitary expertise is to prevent diseases that can be transmitted to humans through products of food (meat, milk, fish, eggs), feed, raw materials (skin, wool, down, wool) obtained from animals. It was formed in the 20th century as an independent science network. Before that, they studied meat science and food hygiene. Veterinary-sanitary expertise is taught in veterinary institutes and veterinary faculties with independent chairs, and is included in the course of food hygiene in medical institutions. Scientific research works on veterinary-sanitary expertise are carried out in the departments of relevant higher educational institutions, in special laboratories of scientific research institutes.
Keywords: Veterinary sanitary expertise; history; mission; study methods